Assessing The Key Physical Capabilities in Striking Combat Sports: Reliability And Reproducibility of A New Test - Baptiste Gusciglio; Jean-Benoit Morin (International Universities Strength and Conditioning Association, 2023)
The rules and the technical aspect of combat sports make it difficult to determine key performance indicators. Therefore, the assessment of striking sports discipline-specific key components may be relevant. This study aims to present a test assessing specifically the fighters striking force-velocity (F-V) capabilities. 10 MMA fighters performed FV (two-point (TP) and multiple-point (MP) methods) and fatigue tests using the landmine punch exercise (LPE) which is considered a specific exercise for striking combat sports. A high within-subject intra-session and inter-session reliability and reproducibility were found for the FV profiles parameters and the fatigue test (most CVs<10%, ICCs>0.67, ES < 0.2 for F0, V0, Pmax, Sfv, Ppeak, Pmean, Pmin and FI%  and r > 0.9). Moreover, the TP and MP methods showed high validity and agreement (r >0.88 and ES <0.37). The novel LPE test presented in this pilot study is a highly reproducible tool for evaluating both mechanical and anaerobic components specific to the discipline. Athletes and coaches may use this test to better understand striking performance in combat sports.